KASUS PENYELESAIAN BATAS LAUT ANTARA INDONESIA DAN MALAYSIA - selpi, selpiana br nababan; Jamba, Padrisan (LPPM Universitas Putera Batam, 2024)
The sovereignty dispute over the Sipadan-Ligitan islands between Indonesia and Malaysia underscores the need for enhanced legal expertise and active participation from all parties in seeking fair and sustainable solutions. Limited access to quality international legal counsel has hindered Indonesia's ability to effectively present its claims, while Malaysia has capitalized on the situation. Persistent disagreements over the islands' ownership and status highlight the importance of strengthening diplomatic efforts and legal capabilities to address complex territorial disputes in Southeast Asia. Greater investment in international legal proficiency and diplomatic initiatives is essential to protect Indonesia's national interests and prevent exploitation by external parties.